The functional significance of dentin sialoprotein-phosphophoryn and dentin sialoprotein. Issue 4 (December 2018) - Ritchie, Helena
Abstract Phosphophoryn (PP) and dentin sialoprotein (DSP) are the most dominant non-collagenous proteins in dentin. PP is an extremely acidic protein that can function as a mineral nucleator for dentin mineralization. DSP was first identified in 1981, yet its functional significance is still controversial. Historically, these two proteins were considered to be independently synthesized and secreted by dental pulp cells into the developing dentin matrix. However, with the identification of the DSP coding sequence in 1994, followed 2 years later by the finding that the PP coding sequence was located immediately downstream from the DSP sequence, it became immediately clear that DSP and PP proteins were derived from a single DSP-PP (i.e., dentin sialophosphoprotein, DSPP) transcript. Since DSPP cDNA became available, tremendous progress has been made in studying DSP-PP mRNA distribution and DSP generation from the DSP-PP precursor protein at specific cleavage sites by protease tolloid-related-1 (TLR1) or bone morphogenetic protein 1 (BMP1). The functions of DSP-PP and DSP were investigated via DSP-PP knockout (KO) and DSP knockin in DSP-PP KO mice. In addition, a number of in vitro studies aimed to elucidate DSPP and DSP function in dental pulp cells. Endodontics: Functional significance of dentin sialoprotein-phosphophoryn and dentin sialoprotein Along with phosphophoryn (PP), dental sialoprotein (DSP) is the dominant non-collagen protein in dentin, and in vitro studies have demonstrated that DSP is involved in inducing the differentiation of dental pulp cells into odontoblast-like cells, which form dentin. PP is known to be involved in the mineralization of dentin, but the functional significance of DSP had been controversial. Helena Ritchie of the University of Michigan School of Dentistry conducted a review of studies investigating the derivation, function and distribution of PP and DSP. It was originally thought that PP and DSP were synthesized independently; later, it became evident that they derive from a single DSP-PP gene. Wider DSP-PP distribution in various tissues, including kidney and salivary glands, and DSP or PP expression in non-mineralized tissues suggest that the proteins may have functions other than mineralization.